The management of a complex elbow injury with transection of the brachial artery - Nekkanti, Supreeth; Siddartha, Arunodhaya; Sastry, Purushotham; M., Prakash; Verma, Anubhav (International Journal of Research in Orthopaedics, 2017)
Elbow dislocations are commonly encountered cases by orthopaedic surgeon. Vascular injury accompanying an elbow dislocation is a surgical challenge. The authors report a rare complication of complete transaction of the brachial artery following a posterior dislocation of the elbow joint. A fifty-year old male suffered a road traffic accident during which he injured his left elbow. Radiographs confirmed a posterior dislocation of the elbow joint. However the radial and ulnar pulse very not palpable. Arterial doppler confirmed injury to brachial artery. The patient was successfully treated and regained full functional use of his left upper limb. The aim of this report is to help readers understand why a vascular injury occurs following an elbow dislocations. A successful management of such injuries revolves around a prompt clinical diagnosis and early repair.